The Influence of Education, Training and Local Culture on the Performance of Young Entrepreneurs in the New Normal Era in Minahasa District - Trang, Irvan; Tawas, Hendra N.; Murni, Sri (Archives of Business Research, 2023)
Quality human resources are human resources who have good knowledge, abilities, skills and attitudes at work. Entrepreneurs are human resources who are directly involved in carrying out their business activities. To create that, entrepreneurs need to get education, training and pay attention to their local culture so they can improve their performance in maintaining and developing their business. This is of course in line with the current phenomenon, where many businesses are bankrupt, closed, out of business in the current era of the Covid 19 pandemic, including in Minahasa Regency, where there are ± 250 young entrepreneurs involved in various different types of businesses affected by the outbreak. The purpose of this research is to analyze and study and develop a variable and instrument that is able to identify what influences the performance of young entrepreneurs in Minahasa Regency. The stages of the method used in the approach and achievement of this research are observation, identifying samples in this case respondents (entrepreneurs) in Minahasa Regency, using survey methods, distributing questionnaires and providing open-ended questions to get accurate results, then processing data and evaluate the results obtained for seminars and publication. After the results are obtained, the results of this study will make a positive contribution to all stakeholders (Academition, Businessman, Government)